2022
DOI: 10.1002/slct.202104489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Naphthalenylmethylen Hydrazine Derivatives as Potent Inhibitors on, Antiatherogenic Enzymes, Paraoxonase I and Acetylcholinesterase Activities

Abstract: Acetylcholinesterase (AChE) and paraoxonase 1 (PON1) are two important serum ester hydrolases that have antiatherosclerotic effect by inhibiting the oxidation of lipid peroxides. In addition, AChE inhibitors are target molecules for the treatment of Alzheimer's. Naphthalene derivatives are important molecules in the field of pharmacology due to their wide range of biological activities. In this study, the inhibition effects of naphthalenylmethylen hydrazine derivatives on these two metabolic enzymes were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…They showed that all complexes exhibited weaker inhibitory properties than their corresponding benzimidazolium salts. Shirinzadeh et al [ 32 ] determined the inhibitory effects of naphthalenylmethylen hydrazine derivatives on the PON1 enzyme. IC 50 values of these molecules were found in the range of 0.158–6.862 μM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that all complexes exhibited weaker inhibitory properties than their corresponding benzimidazolium salts. Shirinzadeh et al [ 32 ] determined the inhibitory effects of naphthalenylmethylen hydrazine derivatives on the PON1 enzyme. IC 50 values of these molecules were found in the range of 0.158–6.862 μM.…”
Section: Resultsmentioning
confidence: 99%
“…[30,31] The enzymatic activity was detected in a reaction mixture consisting of 1 mM paraoxon-ethyl, purified enzyme solution, and glycine-sodium hydroxide solution (50 mM, pH 10.5) containing CaCl 2 (1 mM). [32][33][34] Analyses of paraoxonase activity were performed spectrophotometrically at 412 nm, and the activities were computed using the molar absorptivity coefficient (ε = 18,290 M −1 cm −1 ) of 4-nitrophenol, as in previous assays. [35][36][37] The IC 50 values, the inhibitory concentrations that reduce enzyme activity by 50%, were calculated by plotting activity versus inhibitors.…”
Section: Biological Studiesmentioning
confidence: 99%
“…The thiocholine formed reacts with DTNB and forms the yellow 5‐thio‐2‐nitrobenzoate anion. This molecule gives maximum absorbance at 412 nm wavelength [22] . A percent activity versus inhibitor concentration graph was drawn for the designation of the inhibition efficacy of each the new N ‐substituted‐( p ‐chlorophenyl)pyridazin‐3(2 H )‐one 5 ( a – f ) on the AChE and BChE enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…This molecule gives maximum absorbance at 412 nm wavelength. [22] A percent activity versus inhibitor concentration graph was drawn for the designation of the inhibition efficacy of each the new Nsubstituted-(p-chlorophenyl)pyridazin-3(2H)-one 5(a-f) on the AChE and BChE enzymes. The IC 50 values were obtained from these graphs.…”
Section: Cholinesterase (Bche) Enzyme Inhibition Studiesmentioning
confidence: 99%
“…In a reaction combination including 1 mM paraoxon-ethyl, pure enzyme solution, and glycine-sodium hydroxide solution (50 mM, pH 10.5) containing CaCl 2 , enzymatic activity was identified as in prior research. [48][49][50] As in earlier tests, paraoxonase activity was measured spectrophotometrically at 412 nm [51][52][53] and the activities were calculated using the molar absorptivity coefficient (ε = 18,290 M −1 cm −1 ) of p-nitrophenol. [54][55][56] Plotting activity versus inhibitors yielded the half maximal inhibitory concentration values, inhibitory doses limiting enzyme activity by 50%.…”
Section: Biological Studiesmentioning
confidence: 99%